ANALISIS YURIDIS MENGENAI BATAS MINIMUM & MAKSIMUM USIA CALON PRESIDEN DAN CALON WAKIL PRESIDEN BERDASARKAN UU NO. 7 TAHUN 2017 - Ersa Nabila; Metta suryani; Rodiatun Adawiyah (CV Rewang Rencang, 2024)
The purpose of this study is to find out what causes the public to disagree with the ML decision and to find out whether the constitutional decision in the general election is correct or only in favor of personal interests. This study is a type of Data Research using an empirical legal approach. The data sources are obtained from Social Media, the Internet and books. The results of the study are that there is an intolerable injustice that limits the minimum age of presidential/vice presidential candidates to a minimum of 40 years, as an age restriction that is only placed at a certain age without opening up equivalent alternative requirements, one form of intolerable injustice in the presidential and vice presidential election contest.